Coenzyme A and protein CoAlation levels are regulated in response to oxidative stress and during morphogenesis in Dictyostelium discoideum - Aloum, Lujain (Biochem Biophys Res Commun, 2019)
Dictyostelium discoideum (D. discoideum) is a simple eukaryote with a unique life cycle in which it differentiates from unicellular amoebae into a fruiting body upon starvation. Reactive oxygen species (ROS) have been associated with bacterial predation, as well as regulatory events during D. discoideum development and differentiation. Coenzyme A (CoA) is a key metabolic integrator in all living cells. A novel function of CoA in redox regulation, mediated by covalent attachment of CoA to cellular proteins in response to oxidative or metabolic stress, has been recently discovered and termed protein CoAlation. In this study, we report that the level of CoA and protein CoAlation in D. discoideum are developmentally regulated, and correlate with the temporal expression pattern of genes implicated in CoA biosynthesis during morphogenesis. Furthermore, treatment of growing D. discoideum cells with oxidising agents results in a dose-dependent increase of protein CoAlation. However, much higher concentrations were required when compared to mammalian cells and bacteria. Increased resistance of D. discoideum to oxidative stress induced by H(2)O(2) has previously been attributed to high levels of catalase activity. In support of this notion, we found that H(2)O(2)-induced protein CoAlation is significantly increased in CatA-deficient D. discoideum cells. Collectively, this study provides insights into the role of CoA and protein CoAlation in the maintenance of redox homeostasis in amoeba and during D. discoideum morphogenesis.